The position of the relationship between philosophy, philosophy and legal philosophy - Supriarno,; Abdul Rachmad Budiono,; Setyo Widagdo,; Moh. Fadli, (Technium Social Sciences Journal, 2020)
Science is a process and a product of knowledge which contains explanations of various phenomena that are the object of it’s study. Philosophy is a science with it’s own degree, it tries to find and find truth at a radical level, trying to find the deepest causes of everything that exists as far as it exists. Philosophy of science and philosophy of law are part of philosophy. Philosophy of science is a science of philosophy whose object is a particular science, it examines all matters relating to the practice of science while philosophy of law is a philosophy of philosophy whose object is legal norms, it studies all matters relating to law. Based on this fact, philosophy is the parent of the philosophy of science and philosophy of law.